Cognitive control over motor output in Tourette syndrome - Jung, Jeyoung; Jackson, Stephen R.; Parkinson, Amy; Jackson, Georgina M. (Elsevier, 2013)
Tourette syndrome [TS] is a neurodevelopmental disorder characterised by chronic vocal and motor tics. TS has been associated with dysfunctional cognitive (inhibitory) control of behaviour, however the evidence for this, beyond the occurrence of tics, is scant. Furthermore, in recent studies of uncomplicated TS, it has been shown that adolescents with TS exhibit paradoxically enhanced cognitive control of motor output, consistent with the typical developmental profile of increasing control of tics during adolescence. Here we present arguments, together with new data, that run counter to the widely held view that prefrontal cortex (PFC) is the source of inhibitory task-control signals. Instead, we argue that PFC should be viewed as a source of facilitatory signals that bias competition in brain areas more directly involved in motor execution. Importantly, we argue that in TS, over-activation of PFC may contribute to the hyperexcitability of motor regions and the occurrence of tics; and that compensatory changes, leading to enhanced cognitive control in TS, may primarily be implemented by distributed changes in local cortical excitability.